2003
DOI: 10.1046/j.1095-8649.2003.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Stock discrimination and movements of narrow‐barred Spanish mackerel across northern Australia as indicated by parasites

Abstract: The parasite fauna of Spanish mackerel Scomberomorus commerson from 10 sites across northern Australia and one site in Indonesia, was examined to evaluate the degree of movement and subsequent stock structure of the fish. Kupang fish (Indonesia) had very few Terranova spp., Grillotia branchi, Otobothrium cysticum or Pterobothrium sp. compared to Australian fish, indicating that no Australian fish enter the Kupang fishery. Univariate and discriminant function analysis of four ‘temporary’ parasite species, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 19 publications
2
55
1
1
Order By: Relevance
“…In a similar study on the closely related S. commerson, Moore et al (2003) found using canonical analysis that there were at least 6 parasitologically distinct stocks of S. commerson across northern Australia, a finding that was supported by otolith isotope analysis on the same fish species ). In S. semifasciatus parasite differences across northern Australia were less marked.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In a similar study on the closely related S. commerson, Moore et al (2003) found using canonical analysis that there were at least 6 parasitologically distinct stocks of S. commerson across northern Australia, a finding that was supported by otolith isotope analysis on the same fish species ). In S. semifasciatus parasite differences across northern Australia were less marked.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, they have been used successfully by many authors in earlier studies (e.g. Moore et al, 2003;Williams and Lester, 2006;MacKenzie et al, 2008). To accurately identify these parasites fresh samples were collected from the eastern Gulf of Carpentaria and the east coast of Queensland.…”
Section: Methodsmentioning
confidence: 99%
“…At that time the parasites were thought to be directly transmitted but recent studies show that they almost certainly require an intermediate host (Kent et al, 2001) and therefore do not conform to his condition. Many workers have found that the best markers are larvae or juveniles of anisakids and trypanorhynchs, parasites that require at least three host species to complete their life cycles (Boje et al, 1997;MacKenzie and Abaunza, 1998;Moore et al, 2003) so the one-host recommendation should be abandoned.…”
Section: Introductionmentioning
confidence: 99%
“…The author reported that Indonesia is at the centre of the diversity of this group of fish worms, and predatory fish especially can be highly infected. Lester et HELMINTHOLOGIA, 45, 1: 3 -12, 2008 Molecular genotyping of Anisakis Dujardin, 1845 (Nematoda: Ascaridoidea: Anisakidae) larvae from marine fish of Balinese and Javanese waters, Indonesia Moore et al (2003) and Latama (2006) used fish parasites to distinguish between Indonesian and Australian stocks of the narrow-barred Spanish mackerel Scomberomorus commerson, and Jakob and Palm (2006) studied 5 commercially important fish species off the south-western Java coast for fish parasites. The latter recorded 38 different parasite species, among these was Anisakis sp., reaching a prevalence of 100 %.…”
Section: Introductionmentioning
confidence: 99%